2004
DOI: 10.1177/0363546503261714
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Soft Tissue Femoral Fixation Devices for Anterior Cruciate Ligament Reconstruction

Abstract: The interference screw and the Rigidfix fixation demonstrated inferior fixation biomechanics compared to the Bio-Transfix and the Endobutton techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
160
4
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(181 citation statements)
references
References 38 publications
7
160
4
7
Order By: Relevance
“…27 Harilainen et al's study of ACL reconstruction with hamstring tendons, the arthrometry results and IKDC scores of cross-pin versus metal interference screw femoral fixation were compared at 1 or 2 year follow-up examinations, and no statistically significant difference was found between both groups. 28 There is no consensus on femoral fixation of the hamstring tendon in anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 98%
“…27 Harilainen et al's study of ACL reconstruction with hamstring tendons, the arthrometry results and IKDC scores of cross-pin versus metal interference screw femoral fixation were compared at 1 or 2 year follow-up examinations, and no statistically significant difference was found between both groups. 28 There is no consensus on femoral fixation of the hamstring tendon in anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 98%
“…Para evitar que os dados de força versus deslocamento sejam poluídos, tentou-se ao máximo limitar as variáveis do sistema [8][9][10] . Sendo assim, foi necessário o desenvolvimento de um sistema de garras e simuladores de fixação com alta resistência, para que a falha ocorresse no tendão, evitando-se novas variáveis.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…The most rapid healing time at the insertion sites found with this graft choice with 360 degree bone-to-bone (block-totunnel) union occurs within 4 to 6 weeks, similar to fracture healing 12,13 . Even though some of the biomechanical and clinical studies came up with comparable pullout strength for cross pins [14][15][16][17][18] , a limited number of studies showed increased slippage and inferior pull out strength 19 . Even though there are some studies to evaluate Rigidfix femoral fixation in hamstring tendon there are no clinical studies to show the functional outcome of cross pin femoral fixation in BTB autograft in literature.…”
Section: Introductionmentioning
confidence: 99%